Overlap or Outlier? Granulomatosis With Polyangiitis With Eosinophilia: A Case Report and Diagnostic Insight - Sinen Tadesse Zeleke MD; Syeda Ramsha Zaidi MD; Ademsegd Isac Gebremedhen MD; Melinda Becker MD (Journal of Investigative Medicine High Impact Case Reports)
Granulomatosis with polyangiitis (GPA) and eosinophilic GPA (EGPA) are distinct yet overlapping forms of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis, each with unique clinical features. GPA typically involves necrotizing granulomatous inflammation of the upper and lower respiratory tracts and is strongly associated with cytoplasmic ANCA (c-ANCA) and PR3-ANCA positivity, while EGPA is characterized by eosinophilia, asthma, and vasculitis. Rare cases of GPA can present with eosinophilia, complicating the distinction between these entities and raising the possibility of a GPA/EGPA overlap syndrome. We present the case of a 40-year-old female with a history of rheumatoid arthritis and recurrent pneumonia, admitted with worsening dyspnea, peripheral eosinophilia, and high titers of anti-PR3-ANCA. Bronchoalveolar lavage confirmed eosinophilic infiltration, leading to an initial diagnosis of GPA with eosinophilia. The patient responded well to corticosteroids, rituximab, and avacopan, with significant clinical improvement. This case underscores the importance of integrating clinical, serologic, and histopathologic findings when diagnosing ANCA-associated vasculitis, particularly in patients with eosinophilia and asthma-like symptoms. Recognizing GPA with eosinophilia as distinct from true GPA/EGPA overlap is crucial for prognosis and treatment decisions.